HIGHER EDUCATION IN INDIA: TRANSITION FROM SOCIALISM TO CAPITALISM - Mishra, Ravishri; Sirguroh, Momina (European Scientific Journal, ESJ, 2014)
Socialism in India emerged during the 20th Century as part of the Independence movement and gained strong hold as it espoused the causes of the under privilege section of the society. It influenced the principle economic and social policies of the Indian government after independence until the 1990’s when India took a step towards a neo-liberal economy. The hegemony of neo liberal ideology as reflected in the adoption of free trade, market economy, privatization and predominance of corporate culture that actually calls for progressive decrease of state involvement in the governance, finance and administration of the higher education system in India hijacked the idea of a welfare state. This led India to gradually drift away from socialism to capitalism. This paper outlines the impact of neo-liberal capitalism on Education. It examines neoliberalism as coerced concepts of corporatization and commercialization of higher education in India. It highlights that neoliberalism would polarised the society.